2013
DOI: 10.1021/es400615q
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Induced Deregulation of microRNA Expression in the Zebrafish Olfactory System

Abstract: Although environmental trace metals, such as copper (Cu), can disrupt normal olfactory function in fish, the underlying molecular mechanisms of metal-induced olfactory injury have not been elucidated. Current research has suggested the involvement of epigenetic modifications. To address this hypothesis, we analyzed microRNA (miRNA) profiles in the olfactory system of Cu-exposed zebrafish. Our data revealed 2, 10, and 28 differentially expressed miRNAs in a dose-response manner corresponding to three increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 66 publications
2
25
0
Order By: Relevance
“…The first definition of epigenetics, as 'the causal interactions between genes and their products, which brings the phenotype into being', was provided by Waddington (1939) long before any mechanistic understanding of the relevant processes had developed. This definition has since been refined.…”
Section: Overview Of Epigenetic Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first definition of epigenetics, as 'the causal interactions between genes and their products, which brings the phenotype into being', was provided by Waddington (1939) long before any mechanistic understanding of the relevant processes had developed. This definition has since been refined.…”
Section: Overview Of Epigenetic Mechanismsmentioning
confidence: 99%
“…Consequently it has been proposed that rapid adaptation may be more strongly linked to epigenetic processes in the development of locally adapted phenotypes at polluted sites (Kovalchuk et al 2003). (Kure et al 2013;Wang et al 2013;Song et al 2012) and histone modifications (Raut and Sainis 2012;Mondal et al 2016). Changes in microRNA expression have further been shown to be involved in metabolism following starvation and the transfer of longevity (Greer et al 2011;Katz et al 2009;Rechavi et al 2014).…”
Section: Evidence For Long-term Effects Induced By Radiation On the Ementioning
confidence: 99%
“…The present study also indicated that 16 miRNAs were differentially expressed between the control and Cu-treated group. Similarly, Wang et al [ 23 ] also found that waterborne Cu exposure influenced miRNAs expression in other fish. Moreover, GO and KEGG analysis indicated that these differentially expressed miRNAs were involved in ether lipid metabolism pathway, glycerophospholipid metabolism pathway and linoleic acid metabolism pathway, which seemed to be important pathways under Cu exposure.…”
Section: Discussionmentioning
confidence: 90%
“…In a zebrafish model, copper induced deregulation of miRNAs (from olfactory system tissues) involved in neurogenesis (e.g., let-7, miR-7a, miR-128, and miR-138), which suggests a role for miRNAs in copper-mediated toxicity via interference with neurogenesis processes [76]. …”
Section: Known Neurotoxic Xenobiotics Perturb Mirnas In the Brainmentioning
confidence: 99%